The role of coastal communities in transboundary marine resources management in selected Sub-Saharan African cities - Oluwayemisi, Ogunleye (UIN Sunan Ampel Surabaya, 2026)
This paper examines the critical role of coastal communities in managing transboundary marine resources across selected Sub-Saharan African cities, including Lagos, Abidjan, Accra, Mombasa, and Cape Town. Using a systematic review of recent studies, reports, and policy documents, the research investigates governance frameworks, environmental challenges, and the integration of indigenous and local knowledge (ILK) in shared marine ecosystems. Findings reveal that, while regional conventions provide legal foundations for cooperation, weak enforcement, limited community participation, and socio-political inequalities hinder effective transboundary governance. Coastal communities face mounting environmental pressures from climate change, pollution, and habitat degradation, all of which threaten livelihoods and biodiversity. The study highlights successful community-based management initiatives and underscores the importance of inclusive governance, capacity building, and co-management approaches in enhancing resilience. Policy recommendations advocate for stronger stakeholder engagement, integration of ILK, and interdisciplinary research to support sustainable marine resource management. This work contributes to understanding the socio-ecological complexities of marine governance and offers practical pathways for strengthening community involvement in transboundary resource stewardship in Sub-Saharan Africa.